Path Analysis on Writing Anxiety, Writing Attitude, Language Awareness, and Writing Achievement of University Students - Dhena Usthiana Haryanti; Fathor Rasyid; Sri Wahyuni (English Learning Innovation (englie), 2022)
During the teaching and learning process in writing context, EFL learners have their own intrinsic problems. They tend to experience some psychological tensions such as writing anxiety, writing attitude and language awareness. In line, some academical issues they need to handle in writing context are text organization, grammar, spelling, punctuation and ideas development. The aim was to find out the direct and indirect contribution among the variables. Thus, writing anxiety and writing attitude were the exogenous variable, then language awareness as mediated variable, while the writing achievement as the endogenous variable. This study applied the combination of multiple regression and mediated model as a part of Path Analysis. There were four instruments used, namely SLWAI, ATWQ, LALQ, and TOEFL Independent Writing Test. These instruments were fulfilled by 100 participants of fourth semester English Department students. The data was collected online through Google Form, Google Meet and personal chat on WhatsApp. The result shows that there was low significant direct contribution of writing anxiety toward writing achievement. Meanwhile, there was no significant direct contribution of writing attitude toward writing achievement. In addition, there was a significant direct contribution of language awareness toward writing achievement. Besides, the result of indirect contribution revealed, there was no indirect contribution of writing anxiety through writing attitude toward writing achievement. Then, the indirect contribution of writing attitude through language awareness toward writing achievement was found out significant. Lastly, it was revealed that there was no indirect contribution of writing anxiety through language awareness toward writing achievement.